Towards a Web Based Adaptive and Intelligent Tutoring System - Jose Noguera; Foluso Emmanuel Ayeni; Sena Okuboyejo; Sumana Adusumilli (International Journal of Computing and Informatics (IJCANDI), 2017)
E-Learning provides convenient and cost effective education. Learning management systems (LMSs) like Blackboard and Moodle are common platforms. They support teachers in several ways including creating online courses. However, these systems do not consider the individual differences of students and do not adapt according to their needs. To be highly useful, these systems should be built on self-contained and reusable learning objects (LOs) using adaptive hypermedia technologies. Adaptive hypermedia systems apply different forms of user models to contents and links. This paper presents the architecture, design and significance of web-based adaptive and intelligent learning system that optimizes individual learning performance. The system efficiently integrates reusable learning objects and adaptive hypermedia technologies.